Classic Papers in Modern Diagnostic Radiology - Thomas, Adrian M.K.; Banerjee, Arpan K.; Busch, Uwe.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2005)
I am very pleased to have been asked to write the foreword to this book. The technical advances in diagnostic radiology in the last few decades have transformed clinical practice and have been nothing short of astonishing. The subject of diagnostic radiology is now very large and radiology depa- ments are involved in all areas of modern patient care.The defining event in m- ern radiology,and arguably the most significant development in radiology since Wilhelm Röntgen discovered X-rays, was the invention of the CT scanner in the 1970s.The CT scanner introduced modern cross-sectional imaging and also di- tal imaging.We now have MRI and ultrasound and these techniques are replacing many traditional X-ray procedures.The developments in radiology have been the result of a fruitful interaction between the basic sciences, clinical medicine and the manufacturers. This can be seen by looking at the various sources of these publications. Change is produced by the interactions between the various dis- plines. The editors have had a very difficult task in selecting the key discoveries and descriptions.The radiological literature is very large.Medical imaging continues to develop rapidly and these papers are the foundations of our current practice.
Computer Tomography -- Magnetic Resonance Imaging -- Ultrasound -- Digital Imaging -- PACS -- Contrast Agents -- Angiography and Interventional Radiology -- Mammography.
Keywords: Medicine; Radiology; Interventional radiology; Cardiology; Medicine & Public Health; Imaging / Radiology; Diagnostic Radiology; Interventional Radiology; Ultrasound; Cardiology; Electronic books